Estimation of the genetic parameters in the irrigated rice population CNA-IRAT 4/0/3 - Peixoto de Morais, Orlando; Silva, José Carlos; Cruz, Cosme Damião; Regazzi, Adair José; de Carvalho Ferreira Neves, Péricles (Pesquisa Agropecuaria Brasileira, 1997)
The estimation of genetic parameters of a population helps to elucidate the nature of gene action involved in the inheritance of traits and to establish the basis to choose the most appropriate breeding procedures. The present work aimed to estimate the following parameters for the population CNA-IRAT 4/0/3: components of genetic variance, heritability, coefficient of genetic variation and variation index. The degree of association among some traits was also evaluated. Data were obtained from 59 self pollinated half-sib families and from 60 S0:2, evaluated in Goianira, GO, Brazil, in a complete randomized block design with two replications. Non-additive components of genetic variance are not relevant for plant height, panicle length and 100 seed weight. For grain production and panicle number per plant, which show significant estimates for dominante variance, the heritability coefficients and variation indexes are of intermediate to low magnitudes. In spite of these two values, they may suffer substantial modifications in their averages due to their coefficients of genetic variation being as high as those of more heritable traits.